A quality improvement project in a hospital in rural Nepal – improving infection control practice using the ‘Plan, Do, Study, Act’ (PDSA) cycle - Kong, Kelvin; Kong, Sarah (International Journal of Infection Control, 2013)
High quality infection control practice is fundamental to the provision of safe healthcare. In countries where healthcare is less developed, this notion is less well recognized. The Plan, Do, Study, Act (PDSA) cycle is an implementation strategy used for changing healthcare practice and forms a framework for testing multiple ideas on a small scale, before implementation of change on a larger scale. Our aim was to improve infection control standards in a rural district hospital in Nepal using the PDSA cycle. Potential areas for improvement within infection control practice were first identified. Patient contacts and hand washing episodes were then recorded on the ward round in a tally chart method on the medical wards, which was deemed to reflect infection control standards. The three week intervention period included healthcare staff education and provision of alcohol gel. Data was re-collected after the intervention. 18 hand cleaning episodes were observed in 134 patient contacts in the initial one week observation period, hence 13.4% of patient contacts fulfilled appropriate hand hygiene practice. In the post intervention period, 69 hand cleaning episodes were observed in 142 patient contacts, giving rise to a 48.6% success rate. The overall percentage of appropriate hand hygiene performed therefore improved 3.6 fold. Our results confirmed an improvement in the hand hygiene practice of hospital staff. We extrapolated these results to a probable reduction in healthcare-associated infection for the hospital and local population. The study demonstrates that the PDSA cycle can be an effective tool irrespective of resources available.